1989
DOI: 10.1111/j.1365-2621.1989.tb08557.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological, Chemical, and Physical Changes in Fresh, Vacuum‐Packaged Pork Treated with Organic Acids and Salts

Abstract: The effects of selected organic acids and salts on microbial numbers, pH, exudate, and color were studied for vacuum-packaged, fresh pork chops. Pork chops were dipped for 2 min in (vhr) 1% acetic acid, 1% acetic/l% lactic acid, 1.5% acetic/l.5% sodium acetate, 3% acetic/ 3% sodium ascorbate, 3% acetic/2% NaCl or sterile, distilled water before being vacuum-packaged and stored at 2" -4°C for 6 weeks. Treatments containing 3% acetic acid resulted in lower aerobic microbial numbers (PcO.05) and effectively inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
27
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 14 publications
10
27
1
Order By: Relevance
“…Those findings are in accordance with those reported here, which showed that although 3% lactic acid was markedly more effective that smaller doses in suppressing the growth of S. aureus, the off-odour intensity and black discoloration of the sheep meat kept at a refrigeration temperature of 4°C precludes the use of 3% lactic acid as an antimicrobial. These results are not in accordance with Mendonca et al (1989), who revealed that a mixture of 1% acetic acid and 1% lactic acid damaged the colour of vacuum-packed pork chops. Gill and Baker (1998) reported that sheep meat had a mean count of 4.6 log 10 TVC CFU/cm 2 in different parts of the carcass during the post-washing phase in the abattoir, a value which is close to the results of Bhandare et al (2007) who reported 5.13 ± 0.58 log CFU/cm 2 .…”
Section: Food Technology and Economy Engineering And Physical Propercontrasting
confidence: 55%
“…Those findings are in accordance with those reported here, which showed that although 3% lactic acid was markedly more effective that smaller doses in suppressing the growth of S. aureus, the off-odour intensity and black discoloration of the sheep meat kept at a refrigeration temperature of 4°C precludes the use of 3% lactic acid as an antimicrobial. These results are not in accordance with Mendonca et al (1989), who revealed that a mixture of 1% acetic acid and 1% lactic acid damaged the colour of vacuum-packed pork chops. Gill and Baker (1998) reported that sheep meat had a mean count of 4.6 log 10 TVC CFU/cm 2 in different parts of the carcass during the post-washing phase in the abattoir, a value which is close to the results of Bhandare et al (2007) who reported 5.13 ± 0.58 log CFU/cm 2 .…”
Section: Food Technology and Economy Engineering And Physical Propercontrasting
confidence: 55%
“…However, when lactic acid concentration in dipping solution was greater than 3%, or exposure was longer than 1 min, there was some evidence of digestion of the muscle. Mendonca et al (11) found that dipping pork chops into organic acids (lactic acid and acetic acid) increased exudate and was detrimental to meat colour. Lactic acid can exist intrinsically in fish flesh in concentrations of up to 1 g/100 g in dark-fleshed fish (12), produced from glycogen by glycolysis.…”
Section: Discussionmentioning
confidence: 98%
“…Smith et al (1974) found that Longissimus dorsi muscle had become lighter after 28 days of storage, whereas Hall et al (1980) and Schluter et al (1994) found no differences in colour changes in M. longissimus dorsi during storage. Conversely, Mendonca et al (1989) reported that L* and a* values of LT muscles decreased during 4 weeks storage, indicating that pork colour became darker and less red. In the research of Lindahl et al (2006), cold storage for 8 days increased lightness, redness and yellowness of Landrace and Duroc pork, whereas Apple et al (2002) found increased lightness, decreased yellowness, but no effect on redness after 3 weeks of vacuum storage.…”
Section: Effect Of the Storage Time On The Colour Characteristicsmentioning
confidence: 94%